Analysis of IL28B variants in an Egyptian population defines the 20 kilobases minimal region involved in spontaneous clearance of hepatitis C virus. - Vincent Pedergnana; Mohamed Abdel-Hamid; Julien Guergnon; Amira Mohsen; Lénaïg Le Fouler; Ioannis Theodorou; Mostafa Kamal Mohamed; Arnaud Fontanet; Sabine Plancoulaine; Laurent Abel (PLoS ONE, 2012)
Spontaneous clearance of hepatitis C virus (HCV) occurs in ~30% of acute infections. Host genetics play a major role in HCV clearance, with a strong effect of single nucleotide polymorphisms (SNPs) of the IL28B gene already found in different populations, mostly infected with viral genotypes 1 and 3. Egypt has the highest prevalence of HCV infection in the world, which is mostly due to viral genotype 4. We investigated the role of several IL28B SNPs in HCV spontaneous clearance in an Egyptian population. We selected nine SNPs within the IL28B genomic region covering the linkage disequilibrium (LD) block known to be associated with HCV clearance in European populations. These SNPs were genotyped in 261 HCV-infected Egyptian subjects (130 with spontaneous clearance and 131 with chronic infection). The most associated SNPs were rs12979860 (P = 1.6 × 10(-7)) and the non-synonymous IL28B SNP, rs8103142 (P = 1.6 × 10(-7)). Interestingly, three SNPs at the two bounds of the region were monomorphic, reducing the size of the LD block in which the causal variants are potentially located to ∼20 kilobases. HCV clearance in Egypt was associated with a region of IL28B smaller than that identified in European populations, and involved the non-synonymous IL28B SNP, rs8103142.